Quest HW 5-solutions - syed(sms3768 – Quest HW 5 – seckin –(56425 1 This print-out should have 14 questions Multiple-choice questions may

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: syed (sms3768) – Quest HW 5 – seckin – (56425) 1 This print-out should have 14 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. 001 10.0 points Determine the derivative of f when f ( x ) = x 2 sin x + 2 x cos x . 1. f ′ ( x ) = ( x 2 + 2) sin x 2. f ′ ( x ) =- ( x 2 + 2) sin x 3. f ′ ( x ) = ( x 2 + 2) cos x correct 4. f ′ ( x ) =- ( x 2 + 2) cos x 5. f ′ ( x ) = ( x 2- 2) cos x 6. f ′ ( x ) =- ( x 2- 2) sin x Explanation: By the Product Rule, f ′ ( x ) = 2 x sin x + x 2 cos x + 2 cos x- 2 x sin x . Consequently, f ′ ( x ) = ( x 2 + 2) cos x . 002 10.0 points Find the value of f ′ (0) when f ( x ) = (1- 5 x ) − 4 . Correct answer: 20. Explanation: Using the chain rule and the fact that ( x α ) ′ = α x α − 1 , we obtain f ′ ( x ) = 20 (1- 5 x ) 5 . At x = 0, therefore, f ′ (0) = 20 . 003 10.0 points Determine f ′ ( x ) when f ( x ) = x 2 / 3 ( x- 2) 1 / 3 . 1. f ′ ( x ) = 3 x + 2 3 x 2 / 3 ( x- 2) 1 / 3 2. f ′ ( x ) = 3 x- 2 3 x 2 / 3 ( x- 2) 1 / 3 3. f ′ ( x ) = 3 x- 4 3 x 2 / 3 ( x- 2) 1 / 3 4. f ′ ( x ) = 3 x- 4 3 x 1 / 3 ( x- 2) 2 / 3 correct 5. f ′ ( x ) = x- 2 3 x 1 / 3 ( x- 2) 2 / 3 6. f ′ ( x ) = x + 4 3 x 1 / 3 ( x- 2) 2 / 3 Explanation: By the Chain and Product Rules, f ′ ( x ) = 2 3 x − 1 / 3 ( x- 2) 1 / 3 + 1 3 x 2 / 3 ( x- 2) − 2 / 3 = 1 3 braceleftBigg 2( x- 2) 1 / 3 x 1 / 3 + x 2 / 3 ( x- 2) 2 / 3 bracerightBigg . Bringing the right hand side to a common denominator we thus see that f ′ ( x ) = 2( x- 2)+ x 3 x 1 / 3 ( x- 2) 2 / 3 . syed (sms3768) – Quest HW 5 – seckin – (56425) 2 Consequently, f ′ ( x ) = 3 x- 4 3 x 1 / 3 ( x- 2) 2 / 3 ....
View Full Document

This note was uploaded on 04/29/2010 for the course MATH 408K taught by Professor Seckin during the Spring '10 term at University of Texas-Tyler.

Page1 / 6

Quest HW 5-solutions - syed(sms3768 – Quest HW 5 – seckin –(56425 1 This print-out should have 14 questions Multiple-choice questions may

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online